A aplicação tópica de um antagonista TRPA1 reduz a nocicepção e a inflamação em um modelo de lesão muscular traumática em ratos - Kudsi, Sabrina Qader (2023)
Musculoskeletal pain is a widely experienced public healthcare issue, especially after traumatic muscle injury. Besides, it is a common cause of disability, but this type of pain remains poorly managed. However, the pathophysiology of traumatic muscle injury-associated pain and inflammation has not been fully elucidated. In this regard, the transient receptor potential ankyrin 1 (TRPA1) has been studied in inflammatory and painful conditions. Thus, this study aimed to evaluate the antinociceptive and antiinflammatory effect of the topical application of a TRPA1 antagonist in a model of traumatic muscle injury in rats. The mechanical trauma model was developed by a single blunt trauma impact on the right gastrocnemius muscle of Wistar male rats (250– 350 g). The animals were divided into four groups (Sham/vehicle; sham/HC-030031 0.05%; injury/vehicle, and injury/HC-030031 0.05%) and topically treated with a Lanette® N cream base containing a TRPA1 antagonist (HC-030031, 0.05%; 200 mg/muscle) or vehicle (Lanette ® N cream base; 200 mg/muscle) was applied at 2, 6, 12, 24, and 46 h after muscle injury. Furthermore, we evaluated the contribution of the TRPA1 channel on nociceptive, inflammatory, and oxidative parameters. The topical application of TRPA1 antagonist reduced biomarkers of muscle injury (lactate/glucose ratio), spontaneous nociception (rat grimace scale), inflammatory (inflammatory cells infiltration, cytokine levels, myeloperoxidase, and N-acetyl-β-D-glucosaminidase activities), oxidative (nitrite levels and dichlorofluorescein fluorescence) parameters, and mRNA Trpa1 levels in the muscle tissue. Thus, these results demonstrate that TRPA1 may be a promising anti-inflammatory and antinociceptive target in treating muscle pain after traumatic muscle injury.